Bi-layer silk fibroin skeleton and bladder acellular matrix hydrogel encapsulating adipose-derived stem cells for bladder reconstruction. (4th August 2021) - Xiao, Shuwei; Wang, Pengchao; Zhao, Jian; Ling, Zhengyun; An, Ziyan; Fu, Zhouyang; Fu, Weijun; Zhang, Xu
Abstract : A scaffold, constructed from a bi-layer silk fibroin skeleton (BSFS) and a bladder acellular matrix hydrogel (BAMH) encapsulated with adipose-derived stem cells (ASCs), was developed for bladder augmentation in a rat model. Abstract : A scaffold, constructed from a bi-layer silk fibroin skeleton (BSFS) and a bladder acellular matrix hydrogel (BAMH) encapsulated with adipose-derived stem cells (ASCs), was developed for bladder augmentation in a rat model. The BSFS, prepared from silk fibroin (SF), had good mechanical properties that allowed it to maintain the scaffold shape and be used for stitching. The prepared BAM was digested by pepsin and the pH was adjusted to harvest the BAMH that provided an extracellular environment for the ASCs. The constructed BSFS–BAMH–ASCs and BSFS–BAMH scaffolds were wrapped in the omentum to promote neovascularization and then used for bladder augmentation; at the same time, a cystotomy was used as the condition for the control group. Histological staining and immunohistochemical analysis confirmed that the omentum incubation could promote scaffold vascularization. Hematoxylin and eosin and Masson's trichrome staining indicated that the BSFS–BAMH–ASCs scaffold regenerated the bladder wall structure. In addition, immunofluorescence analyses confirmed that the ASCs could promote the regeneration of smooth muscle, neurons and blood vessels and the restoration of physiological function. These results demonstrated that the BSFS–BAMH–ASCs may be a promising scaffold for promoting bladder wall regeneration and the restoration of physiological function of the bladder in a rat bladder augmentation model.